EVALUASI KINERJA SIMPANG TIGA TAK BERSINYAL PASAR IBUH PAYAKUMBUH - Riyaldi Rendra; Surya Eka Priana; Helga Yermadona (Ensiklopedia Research and Community Service Review, 2023)
Abstrack: The Payakumbuh signalless intersection is a busy traffic intersection due to the high volume of vehicles and high side friction caused by market activity. The Pasar Ibuh intersection connects four sub-districts so that many vehicles pass through the intersection which can cause traffic jams and even traffic accidents. This study aims to evaluate the performance of the signalless intersection of Pasar Ibuh Payakumbuh and find alternative solutions to the problems that occur at these intersections. The research method used is to calculate and observe the volume of traffic flow through recording and observing the location of the intersection to find out the geometry of the intersection and existing side barriers. This research concludes that the peak hour of traffic flow at the Pasar Ibuh Payakumbuh intersection occurs at 16:00 - 17:00 WIB. From the analysis results, the capacity value (C) is = 2824.557 smp/hour, traffic flow (Q) is = 2399 smp/hour, delay (D) is = 14.161 seconds/smp, and the degree of saturation value (DS) is = 0.85. Based on the value of the degree of saturation, the performance level of the intersection is not good. The alternative is to prohibit turning right for minor roads. So that the resulting analysis is a capacity value (C) of = 3172.826 smp/hour, traffic flow (Q) of = 2399 smp/hour, delay (D) of = 12.715 seconds/smp, and the degree of saturation (DS) = 0.76, based on the value of the degree of saturation, it can be concluded that the intersection performance is good.Keywords : Signalless Three-way Intersection, Side Barriers, Degree of Saturation, Intersection Performance, Performance Evaluation